La comercialización de energía eléctrica y su incidencia en el desarrollo de las actividades económicas de la corporación nacional de electricidad (CNEL) agencia Buena Fe periodo 2010-2014 - Mendoza Murillo, Elsa Eliana (2015)
This research develops in the CNEL Agency Buena Fe, located in the canton of the same name province of Rivers. This has a population of 63148 inhabitants, of which 38263 are located in urban areas and 12,607 in rural areas. Currently projected to 2015, the total population would be approximately 74115 inhabitants. The objective of this research is to analyze the impact of the sale of electricity in the development of economic activities of the National Electricity Corporation (CNEL) Buena Fe agency during the years 2010-2014. CNEL Buena Fe caters to 13.1% of users Quevedo electric power system, the collected amount grew between 2010 and 2011 to 8.3% annual average, in identical form in 2012, falling to 2.5% in 2014, just as the participation rate of proceeds from the agency between the system was 8.33% in 2011, 8.59% in 2012, 8.19 in 2013, to settle at 7.84% in 2014. The 50.13% of the population believes that the value you pay for consumption through the return is high. Meanwhile this has generated significant revenues that have influenced improving the economic situation of the agency, expressed as 76.27% of respondents. The 78.13% rated current efficient marketing system, produced by modernization, however you need to strengthen it. For 60% of the administrative and operational employees, revenue levels have improved the economic situation of the agency, producing more investment and increased revenues, affecting them positively, as indicated by 40% of the above. According to 40% of those economic activities that produce greater impact in finance is the sale of electricity.